Influence of ferrochromium type on micro and macro tribology behavior of copper metal matrix composites. (June 2023) - Zhou, Haibin; Yao, Pingping; Xiao, Yelong; Liu, Xiubo; Fan, Kunyang; Gong, Taiming; Zhao, Lin; Deng, Minwen; Zhang, Zhongyi
Abstract: Ferrochromium, an important emerging abrasion component, is added to Cu metal matrix composites (Cu-MMCs) to enhance the high-energy braking properties of such composites. This study examined the microstructures, interfacial characteristics, and micro-tribology behaviors of two kinds of ferrochromium, and their effects on the braking performance of Cu-MMCs. The high-carbon ferrochromium (HCF) with higher hardness, consisting of (Cr, Fe)7 C3 and (Cr, Fe)23 C6 -CrFe phases, formed a poor mechanical-diffusion mixed interface with the matrix and exhibited a low coefficient of friction (COF) in micro-friction tests. By cracking or crushing of HCFs, as well as third-body wear debris formed by HCFs, the COF in macro-friction tests was increased, helping Cu-MMCs maintain their braking performance at medium and high breaking energy densities (BEDs). The extra low-carbon ferrochromium (ELCF), consisting of a CrFe phase, generated a diffusion interface with the matrix, exhibited a greater COF, promoted the formation of a tribo-layer at high BED, and provided better wear resistance for Cu-MMCs. The wear mechanisms changed from plowing to severe plastic deformation-induced delamination and oxidation-induced delamination for Cu-MMCs with ELCF and HCF, respectively.